2016
DOI: 10.1155/2016/9872048
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Anchored Titanium Implants in Patients with Auricular Defects: Three Years and 27 Patients’ Experience

Abstract: Different surgical solutions have been proposed for reconstruction of the auricle following loss of the pinna through traumatic injury or neoplastic disease or in patients with congenital defects. Surgical treatment may involve the insertion of an autogenous rib cartilage framework or the use of a porous polymer material inserted into an expanded postauricular flap. Reconstruction with rib cartilage has yielded good results but requires more than one surgical step, and adverse events can occur both at the dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Quality of life (n=14) [4][5][6][7][8][9]32,39,[59][60][61][62][63][64] Condition specific (specific to facial prostheses) (n=6) [4][5][6][7][8][9] Condition specific (not specific to facial prostheses) (n=5) 39,[59][60][61][62] Generic (n=7) 4,5,32,39,59,63,64 Psychologic health (n=6) 4,32,[65][66][67][68] Psychologic health (n=6) 4,32,[65][66][67][68] Psychosocial (n=1) 67 Other patient reported (n=6) 32,41,44,61,69,70 Preference ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality of life (n=14) [4][5][6][7][8][9]32,39,[59][60][61][62][63][64] Condition specific (specific to facial prostheses) (n=6) [4][5][6][7][8][9] Condition specific (not specific to facial prostheses) (n=5) 39,[59][60][61][62] Generic (n=7) 4,5,32,39,59,63,64 Psychologic health (n=6) 4,32,[65][66][67][68] Psychologic health (n=6) 4,32,[65][66][67][68] Psychosocial (n=1) 67 Other patient reported (n=6) 32,41,44,61,69,70 Preference ...…”
Section: Resultsmentioning
confidence: 99%
“…Linear Analog Self-Assessment (LASA) 32 or LASA-12 5 Short Form 8 (SF-8 Health Survey), 5 SF-12 Health Survey, 39,63 or SF-36 Health Survey 4,59 World Health Organization Quality of Life Instrument (WHOQOL-BREF) 64 Psychological Cornell Medical Index Questionnaire 65 Self-designed condition-specific questionnaires created by authors 32,65,67,68 Condition-specific questionnaires modified from Sela and Lowental 1980 66 Psychosocial Childhood Experience Questionnaire 67 Other patient reported Preference Preference for attachment system 44 Appearance/function Nasal Appearance and Function Evaluation Questionnaire 61…”
Section: Genericmentioning
confidence: 99%
“…Multiple surgeries are required for graft harvesting, tissue expansion, and cosmetic revision, increasing the morbidity and risk for complications. Bleeding, infection, and hematoma are more frequent in comparison to an auricular prosthesis at the implant and graft site 49. Moreover, overall patient satisfaction is frequently lower due to inconsistent aesthetic outcomes 505152…”
Section: Auricular Prosthesesmentioning
confidence: 99%
“…Bleeding, infection, and hematoma are more frequent in comparison to an auricular prosthesis at the implant and graft site. 49 Moreover, overall patient satisfaction is frequently lower due to inconsistent aesthetic outcomes. [50][51][52] Variations and inconsistencies in surgical practice paved the way for prosthetic reconstruction.…”
Section: Auricular Prosthesesmentioning
confidence: 99%
“…An Italian study actually showed bleeding, infection, and hematoma to be more frequent with autologous grafting at the implant and graft site than in an auricular prosthesis. 54 Furthermore, patient satisfaction is frequently lower due to inconsistent cosmetic outcomes. 55 If a prosthesis is favored, tragal preservation can help conceal the anterior margin of the prosthesis.…”
Section: Prostheses Auricularmentioning
confidence: 99%